Knocked out by my Nunga-Nungas you'll Laugh Your Knickers off! - Rennison,Louise (London HarperCollins Children's Books, 2006)
Brilliantly funny teenage angst author Louise Rennison's fabby third book on the confessions of crazy but lovable Georgia Nicolson. Now repackaged in a gorgeous new paperback and guaranteed to have the nation laughing their knickers off!
Keywords: Nicolson, Georgia (Fictitious character) -- England -- Teenage girls